2011
DOI: 10.1155/2011/290616
|View full text |Cite
|
Sign up to set email alerts
|

Subpicosecond dynamics in DNA from leaves ofin vitro-grown apple plants: A SERS study

Abstract: Abstract. In this work the SERS total half bandwidths of five genomic DNAs from in vitro-grown apple leaf tissues (Malus domestica Borkh., Fam Rosaceae, cvs. Florina, Rebra, Goldrush, Romus 3 and Romus 4) have been measured. We have shown that surface-enhanced Raman scattering can be used to study the fast subpicosecond dynamics of DNA in the proximity of a metallic surface. The dependencies of the total half bandwidths and of the global relaxation times, on DNA molecular subgroup structure, on the type of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…A confocal Raman microspectroscopic study into the vibrational half bandwidths of molecular subgroups in calf-thymus DNA at pH 7 and pH 3, in the presence of Na + , Ca 2+ and Mg 2+ ions, respectively, was previously reported by us [5]. The bandwidths in the Raman spectra were sensitive to a dynamics active on a time scale ranging from 0.34 to 1.44 ps [5,[7][8][9].…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…A confocal Raman microspectroscopic study into the vibrational half bandwidths of molecular subgroups in calf-thymus DNA at pH 7 and pH 3, in the presence of Na + , Ca 2+ and Mg 2+ ions, respectively, was previously reported by us [5]. The bandwidths in the Raman spectra were sensitive to a dynamics active on a time scale ranging from 0.34 to 1.44 ps [5,[7][8][9].…”
Section: Introductionmentioning
confidence: 70%
“…Studies of relaxation processes in liquids are valuable in providing information about the intermolecular interactions in condensed matter [3]. Raman and infrared spectroscopy offer the most significant information concerning the behaviour of a condensed system on the picosecond timescale [2,9]. Among the techniques available for the study of molecular motions in liquids, Raman scattering has the distinct advantage, that it enables simultaneous analyses of both reorientational and vibrational processes ( [2,3,7,8] and references therein).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results showed that the SERS method could be applied to studying the dynamics of DNA approaching the surface of the metallic substrate, with good perspectives of analyzing interactions of DNA-ligand or changes of DNA structure under environmental stress conditions [ 120 , 121 ]. They extended the application of this SERS method to other plant leaves, such as chrysanthemum, common sundew, edelweiss and so on [ 122 ]. The SERS spectra of genomic DNAs from tomato plants was also collected and the structural changes of DNAs undergoing cryopreservation were discussed [ 123 ].…”
Section: Application On the Detection Of Plant Original Biomoleculmentioning
confidence: 99%